1980
DOI: 10.1159/000117743
|View full text |Cite
|
Sign up to set email alerts
|

Obsessional Personality Traits and ABO Blood Types

Abstract: The relation of ABO blood types to obsessional personality traits, as measured by the Leyton Obsessional Inventory (LOI), was studied in a sample of 600 normal individuals. High scorers of the LOI trait portion demonstrated a significantly lower incidence of phenotype 0 and a significantly higher incidence of phenotypes AB, A and B, taken together, compared to those of a general population sample and the entire study group. Findings of the present study, in conjunction with previous findings concerning a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…'Trouble remembering things'). The results show that symptoms broadly defined as obsessive-compulsive are less severe in patients with blood type O than blood type A, consistent with the three studies by Rinieris and co workers [Rinieris et al, 1978[Rinieris et al, . 1980[Rinieris et al, .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…'Trouble remembering things'). The results show that symptoms broadly defined as obsessive-compulsive are less severe in patients with blood type O than blood type A, consistent with the three studies by Rinieris and co workers [Rinieris et al, 1978[Rinieris et al, . 1980[Rinieris et al, .…”
Section: Discussionsupporting
confidence: 89%
“…In two studies of Greek patients with obsessivecompulsive disorder Rinieris and co-workers find the frequency of blood type O is significantly lower, and that of blood type A is significantly higher, than in the general population [Rinieris et al" 1978[Rinieris et al" , 1983. They also report that blood type O occurs significantly less often than expected among normal persons with obsessional per sonality traits, while blood type A is more common than expected, although not significantly [Rinieris et al" 1980], They suggest that blood type O is associated with factors which protect against the development of obses sive-compulsive symptoms. On the other hand, a study of British patients with obsessive-compulsive disorder reports no difference in the distribution of blood types between patients and controls [McKcon and McColl.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There are many studies that proved the association between blood groups and personality traits. Obsessional personality traits were analyzed among 600 individuals, and the results showed high incidence of A type and low incidence of O in obsessive compulsive patients (Rinieris et al, 1980). A similar analysis was recently performed in Iran that failed tofind any significant relationship between blood types and personality traits (Dibajnia et al, 2014).…”
Section: Personality Traitsmentioning
confidence: 84%
“…The researchers determined that blood group O might be associated with personality traits hindering the development of obsessive-compulsive symptomology. 25 Marutham et al found blood type B individuals to have higher neuroticism scores compared to blood types O and A on the Eysenck Personality Inventory. 26 The present study results resembles to Boyer, Neumann et al, Rinieris et al, Marutham et al, in contrast to Singg S et al blood group O least affected to suicidal tendency.…”
Section: Resultsmentioning
confidence: 99%